Meningkatkan Keterampilan Menulis Dengan Metode Tracing Handwriting Without Tears Untuk Anak Disgrafia Kelas II - Mayang Hira Mardani; Johandri Taufan (Jurnal Penelitian Pendidikan Khusus, 2022)
Writing is a process of pouring main ideas into writing and is also a type of language skill that must be mastered by everyone.Dysgraphia is a learning difficulty characterized by difficulty in expressing thoughts in handwriting Children World Health Organization have dysgraphia may write very slowly , their writing is unreadable , and they may make a lot of mistakes writing down ideas that are in their brains . Tracing Handwriting is a combination of tracing and multisensory methods. Tracing Handwriting is a combination of tracing and multisensory methods. The tracing method is an activity to trace letters by hand or thicken letters with a pencil or other writing utensil. The activity of tracing or bolding letters makes the subject focus on the shape of each letter and think about how to sound the letters. The multisensory method accelerates the development of neurons in the brain associated with letters thereby accelerating and strengthening the formation of cognitive maps.